Changes in the Transcriptome of Human Astrocytes Accompanying Oxidative Stress-Induced Senescence - Crowe, Elizabeth P.; Tuzer, Ferit; Gregory, Brian D.; Donahue, Greg; Gosai, Sager J.; Cohen, Justin; Leung, Yuk Y.; Yetkin, Emre; Nativio, Raffaella; Wang, Li-San; Sell, Christian; Bonini, Nancy M.; et al. (Frontiers in Aging Neuroscience, 2016)
Aging is a major risk factor for many neurodegenerative disorders. A key feature of aging biology that may underlie these diseases is cellular senescence. Senescent cells accumulate in tissues with age, undergo widespread changes in gene expression, and typically demonstrate altered, pro-inflammatory profiles. Astrocyte senescence has been implicated in neurodegenerative disease, and to better understand senescence-associated changes in astrocytes, we investigated changes in their transcriptome using RNA sequencing. Senescence was induced in human fetal astrocytes by transient oxidative stress. Brain-expressed genes, including those involved in neuronal development and differentiation, were downregulated in senescent astrocytes. Remarkably, several genes indicative of astrocytic responses to injury were also downregulated, including GFAP and genes involved in the processing and presentation of antigens by major histocompatibility complex class II proteins, while pro-inflammatory genes were upregulated. Overall, our findings suggest that senescence-related changes in the function of astrocytes may impact the pathogenesis of age-related brain disorders.